Revealing the subtyping of non‐small cell lung cancer based on genomic evolutionary patterns by multi‐region sequencing. (20th October 2020) - Liao, Gaoming; Liang, Xin; Ping, Yanyan; Zhang, Yong; Liao, Jianlong; Wang, Yihan; Hou, Xiaobo; Jiang, Zedong; Dong, Xiaoqiu; Xu, Chaohan; Xiao, Yun
Abstract: Accurately classifying patients with non‐small cell lung cancer (NSCLC) from the perspective of tumor evolution has not been systematically studied to date. Here, we reconstructed phylogenetic relationships of somatic mutations in 100 early NSCLC patients (327 lesions) through reanalyzing the TRACERx data. Based on the genomic evolutionary patterns presented on the phylogenetic trees, we grouped NSCLC patients into three evolutionary subtypes. The phylogenetic trees among three subtypes exhibited distinct branching structures, with one subtype representing branched evolution and another reflecting the early accumulation of genomic variation. However, in the evolutionary pattern of the third subtype, some mutations experienced selective sweeps and were gradually replaced by multiple newly formed subclonal populations. The subtype patients with poor prognosis had higher intra‐tumor heterogeneity and subclonal diversity. We combined genomic heterogeneity with clinical phenotypes analysis and found that subclonal expansion results in the progression and deterioration of the tumor. The molecular mechanisms of subtype‐specific Early Driver Feature (EDF) genes differed across the evolutionary subtypes, reflecting the characteristics of the subtype itself. In summary, our study provided new insights on the stratification of NSCLC patients based on genomic evolution that can be valuable for us to understand the development of pulmonary tumor profoundly. Abstract : The NSCLC patients were grouped into three subtypes based on the genomic evolutionary patterns. The phylogenetic trees among subtypes exhibited distinct branching structures. The molecular mechanisms of subtype‐specific EDF genes differed across the evolutionary subtypes.